Thermal Performance Analysis of Thermosyphon Solar Water Heating System Fitted with a Spiral Tube - Kabas Aziz Hassan, Ra’ad K Mohammed Al Dulaimi (Mathematical Statistician and Engineering Applications, 2022)
The aim of this thesise is work to improve the heat trnsfer of the thermosyphon solar water heater flat plat type experimentaly by adding twisted tap to one tube model and compered the results with two other tubes types to reach the best improvement results in thermal efficincy and exergy. As a result, goal of this study is to produce the best absorbers of solar raddition , from the suggested.The three used tubes models (normal tube,twisted tube and twisted tube fitted with twisted tapes) in a same determinig measurming and arrengment as flat plat.The last type estemite should achieve the highest result.The flat shap is one of the best shapes,that due to it make largest surface area it provides in front of the solar raddition . As a result, a largest amount of solar heat will transfer to the fluid flow inside the tubes.In this work three models of SWH are used. The purpose of inserting the twisted tape was to facilitate contact between the HTF particulate and the tube’s biggest heated surface, which was heated by solar radiation.. This done by the swirel path of the tube, making circlation in motion of HTF, there fore more particales will be contacted with heat tube surface and eventoly, will be mixed with each other. The twisted tapes inside the twisted tube repeate this mothion ,where the circlation in this way will be doubled .This can be effective way to achieve greater heat absorption in less cost and without need extra external device in order to improve the thermal performance of SWH.The three types were tested experimentally for two objectives: high self-circulation and high thermal performance.The test was done by filling the storge tank with water every morning , then took reading as water level reached a stable state inside the tanke. Temperature difference ?T, self circulation , pressure difference ?p, thermal efficiency ?th , exergetic performance ?ex , and Nusselt number Nu were calculation by mathmatical equations.The test was done in Baghdad/Al-Nahrain university .With continuous work [1-30 , 2022 march] and repeated the tests for each model were performed until the most accurate results were obtaind. It was proven that the new design tube model(TTTT) was The most effective one compered to the other types regarding the setled goals. The results showed that the new design had the following measures: (Nu= 913.71),( =0.25%) ,(